Elementary Analysis of Nail Polishes (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Brazil is considered the 4th largest CT&F Market in the world. In 2017, the country earned R$ 102.5 billion, which means an increase of 3.2% over the year 2016. According to Associação Brasileira da Indústria de Higiene Pessoal, Perfumaria e Cosméticos (ABIHPEC), this information is provided by Strategic Research Institute for Consumer Markets, the Euromonitor. The composition of cosmetics produced should be in accordance with the recommendations presented in ANVISA RDC Resolution No. 83 of June, 2016. Prohibited elements in the RDC Resolution No. 83 are Cl, Ni, As, Be, Cd, Cr, I, P, Pb, Hg, Se, Zr, Co, Te, Tl and radioactive substances. The main purpose of this work was to characterize some nail polishes using EDXRF method. The analyses were made using EDXRF method at the Laboratory of Applied Nuclear Physics of the UTFPR. The AMPTEK portable X-ray equipment is composed of mini X-ray tube, model MINI X, with Ag and Au targets, as well as silicon drift detector, SDD-123 model. Qualitative analyses indicate Na, Mg, Al, Si, P, Na, S, Cl, Ca, Ti, Cr, Mn, Fe, Ni, Cu, Zn, Mo, Ba and Bi elements in the nail polishes analyzed. Some prohibited elements such as Cl, Ni and P were presents in nail polishes. It is shows that EDXRF method is very efficient in detecting the chemical elements present in these samples. Besides, these results enable to compare elements presents in sample and recommendation stablish in Resolution No. 83.